Frequency of vacA Genotypes and Cytotoxin Activity in Helicobacter pylori Associated with Low-Grade Gastric Mucosa-Associated Lymphoid Tissue Lymphoma - Miehlke, Stephan (American Society for Microbiology, 1998)
The vacA genotypes s1,m1 and s1,m2 were detected in 44 and 30% of Helicobacter pylori isolates, respectively, from patients with gastric mucosa-associated lymphoid tissue lymphoma, compared to 26 and 56% of isolates, respectively, from individuals with gastritis. The vacA s1 genotype was significantly associated with, but not predictive of, the presence of vacuolating cytotoxin activity.